The Impact of Digital Transformation on SME Productivity in the Digital Economy Era - Surya Ryan Pratamansyah; David M. Warburton (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digital transformation has become a critical driver of productivity growth among Small and Medium Enterprises (SMEs) in the digital economy era. This study aims to analyze the empirical relationship between digital transformation and SME productivity by synthesizing recent scholarly literature and applying a systematic analytical approach. The research adopts a qualitative systematic literature review method based on 30 peer-reviewed journal articles published between 2021 and 2025. The findings indicate that digital transformation significantly improves SME productivity through operational efficiency, innovation capability, resource allocation optimization, and enhanced customer engagement. The analysis reveals that digital tools such as e-commerce, cloud computing, fintech, and digital marketing contribute to process automation and data-driven decision-making. However, the results also show persistent barriers, including low digital literacy, infrastructure limitations, financial constraints, and cybersecurity risks. The study concludes that digital transformation positively influences productivity when supported by organizational readiness, technological capability, and policy support. This research provides theoretical contributions by integrating productivity and digital transformation frameworks and offers practical implications for policymakers and SME managers to design structured digital adoption strategies in emerging economies.